2015
DOI: 10.1101/gr.176099.114
|View full text |Cite
|
Sign up to set email alerts
|

Effect of minichromosome maintenance protein 2 deficiency on the locations of DNA replication origins

Abstract: Minichromosome maintenance (MCM) proteins are loaded onto chromatin during G1-phase and define potential locations of DNA replication initiation. MCM protein deficiency results in genome instability and high rates of cancer in mouse models. Here we develop a method of nascent strand capture and release and show that MCM2 deficiency reduces DNA replication initiation in gene-rich regions of the genome. DNA structural properties are shown to correlate with sequence motifs associated with replication origins and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 49 publications
1
29
0
1
Order By: Relevance
“…Only 6.8% of G4s with loops of 1-7 nt in the genome overlapped with NS LexoG0 peaks, suggesting that the vast majority of G4 motifs are not general determinants of the location of origins of replication. Similarly, it has recently been reported that only one out of seven G4s in the human genome are associated with BrdU NS peaks (Mukhopadhyay et al 2014) and that only ∼5.2% of G4 motifs are associated with nascent strand peaks from a new λ-exo-independent method called "nascent strand capture and release" (NSCR) (Kunnev et al 2015). Therefore, G4s do not appear to be sufficient for origin specification as most G4 motifs are not associated with origin activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only 6.8% of G4s with loops of 1-7 nt in the genome overlapped with NS LexoG0 peaks, suggesting that the vast majority of G4 motifs are not general determinants of the location of origins of replication. Similarly, it has recently been reported that only one out of seven G4s in the human genome are associated with BrdU NS peaks (Mukhopadhyay et al 2014) and that only ∼5.2% of G4 motifs are associated with nascent strand peaks from a new λ-exo-independent method called "nascent strand capture and release" (NSCR) (Kunnev et al 2015). Therefore, G4s do not appear to be sufficient for origin specification as most G4 motifs are not associated with origin activity.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, most of our NS-seq peaks are not near G4 motifs, suggesting that G4s are not necessary for specification of all origins. Likewise, <6% of NSCR peaks had an orientation-specific relationship with G4s (Kunnev et al 2015), and using the orthogonal origin mapping technique of bubble-seq, Mesner et al (2013) found that the majority of bubble-containing fragments lacked G4 motifs. In regions of discordance between bubble-www.genome.org…”
Section: Discussionmentioning
confidence: 99%
“…Adicionalmente a estos marcadores ampliamente conocidos se suman la proteína 2 para el mantenimiento del minicromosoma 2 (Mini-chromosome maintenance protein 2, MCM 2) esta proteína se encuentra en la cromatina durante la fase G1 y define las ubicaciones potenciales para la iniciación de la replicación del ADN, su deficiencia da como resultado la inestabilidad del genoma 34 . La topoisomerasa alfa II (topoisomerase II alpha, TOP2A) que hace parte de una clase importante de enzimas nucleares responsables del mantenimiento de la topología del ADN y están involucradas en la reparación, la transcripción, la replicación y segregación de los cromosomas 35 y por último la alfa actina 4 (Alphaactinin-4 ACTN4) es una proteína de unión a actina que participa en la organización del citoesqueleto, esta reside tanto en el citoplasma como en el núcleo y se asocia físicamente con varios factores de transcripción 36 .…”
Section: Métodos Bioquímicos Para La Detección Y Prevención Del Vphunclassified
“…The developed protocol has been applied to compare SNSs from wild type and minichromosome maintenance protein 2 (MCM2) deficient mouse embryonic fibroblasts (MEFs) [31]. With minor modification NSCR could be used to examine Okazaki fragments by selecting smaller size DNA from sucrose gradients.…”
Section: Introductionmentioning
confidence: 99%
“…NSCR shows good reproducibility between experimental repeats (~90% of the largest 20% of peaks were common to two independent NSCR analyses of MEFs [31]). It may be possible to validate peaks identified by NSCR as origins by determining if peak width correlates with the size of DNAs recovered from sucrose gradients.…”
Section: Introductionmentioning
confidence: 99%